Pemanfaatan Kredit Usaha Rakyat (KUR) untuk Peningkatan Pendapatan Petani Padi Sawah - Kelbo, Rahmawati; Timisela, Natelda R; Kembauw, Esther (Seminar Nasional Lahan Suboptimal, 2024)
Kelbo, R., Timisela, N. R., & Kembauw, E. (2024). Utilization of People's Business Credit (KUR) to increase the income of rice farmers. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 854–864). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of this study was to analyze the utilization of KUR to increase the income of rice farmers. The research was conducted in Waimital Village, West Seram Regency. The research sample consisted of 51 KUR farmer respondents who were taken through a census. The results of a simple regression analysis of the effect of KUR utilization on income show that KUR utilization has a positive effect on income. The regression coefficient value of 0.754 means that income increases by one percent, then KUR utilization will increase by 0.754 percent. Farmers utilize KUR well, so income increases which has an impact on the KUR installment process. The results of multiple regression analysis show that the Adjusted R Square value of 0.992 means that production (X1), seed costs (X2) and labor wages (X3) can explain the income of rice farmers (Y) by 99.2%, while the remaining 0.8% is explained by other factors outside the model. The F-count value of 1975.498> F-table 2.802 means that X1, X2 and X3 simultaneously affect Y. The results of the partial test show that X1 is positive, meaning that if production increases by 1 percent, income will increase by 1.024 percent. The t-count value of 51.817> t-table 2.012 means that the production variable has a significant effect on the income of rice farmers. The seed cost is negative, meaning that if seed costs increase by 1 percent, income will decrease by 0.040 percent. The t-count value of -2.402> t-table of 2.012 means that the seed cost variable has a significant effect on the income of rice farmers. Labor wages are positive, meaning that if labor wages increase by 1 percent, income will increase by 0.027 percent. The t-count value of 2.603> t-table of 2.012 means that the labor wage variable has a significant effect on the income of rice farmers.